PSYCHO-SOCIAL VARIABLES AS CORRELATES OF ACADEMIC RESILIENCE AMONG UNDERACHIEVING SENIOR SECONDARY SCHOOL STUDENTS IN SOUTH-WEST, NIGERIA (2015)
Most public secondary school students in South-west Nigeria are faced with inadequate emotional, financial and social supports in the home and among peers. Most times, such students are without adequate learning materials, a condition which is not favourable for effective learning and that could hamper academic performance. Despite these challenges, these disadvantaged students still demonstrate willingness and desire to succeed in their academic endeavours. However, factors attributable for academic resilience among these students have not been adequately documented in literature. This study, therefore, investigated the influence of psycho-social variables (academic locus of control, academic self-efficacy, academic intrinsic and extrinsic motivation, parental influence, academic test anxiety, peer influence and study habit) on academic resilience of under-achieving Senior Secondary School (SSS) students in Southwest, Nigeria. The study adopted a survey research design of the correlational type. Multistage sampling procedure was adopted in selecting twelve Local Government Areas (LGA) out of one hundred and thirty seven LGAs that made up the six states in Southwest while sixty public secondary schools were selected from the twelve LGAs. Students‘ cumulative academic performance record (JSS3 and SS1) scores was employed in identifying and recruiting three thousand, two hundred and ninety (males = 1726, x = 14.72, SD = 5.33; females: 1564, x =14.95, SD = 2.37) students. Eight outcome measures were used for data collection: Academic Resilience Scale (α = 0.80); Academic Locus of Control Scale (α = 0.75); Academic Self-efficacy Scale (α = 0.69); Academic Motivation Scale (α = 0.85); Parental Influence Scale (α = 0.86); Academic Anxiety Questionnaire (α = 0.75); Peer Influence Scale (α = 0.81) and Study Habit Scale (0.89). Two research questions were answered and eight hypotheses tested at 0.05 level of significance. Pearson product moment correlation and multiple linear regressions were used for data analysis. The psycho-social variables had a significant joint prediction on academic resilience of under-achieving students (F (8,3281) = 130.924) and they jointly accounted for 23.7% to the observed variance in academic resilience. Academic self-efficacy (β =.34), intrinsic academic motivation (β =.20), extrinsic motivation (β =.056), and parental influence (β =.064) had relative contributions to the prediction of academic resilience, while peer influence, academic anxiety, locus of control and study habit did not. Academic self-efficacy (r =.45), intrinsic motivation (r =.40), peer influence (r =.25), parental influence (r =.23) and extrinsic motivation (r =.22) correlated relatively to academic resilience. However, academic test anxiety, locus of control and study habit did not have any significant relationship with academic resilience. Academic self-efficacy, intrinsic academic motivation, extrinsic academic motivation and parental influence were potent predictors of academic resilience among under-achieving senior secondary students. Therefore, these variables should be taken into cognizance by counselling psychologists, teachers, school administrators and parents in improving students‘ academic achievement. Key words: Academic resilience, Under-achieving senior secondary school students, Psycho-social variables, South-west Nigeria. Word count: 452